2020
DOI: 10.3892/ijmm.2020.4571
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina protein promotes skin wound repair in a mouse model of full-thickness dermal excisional wound

Abstract: The skin protects body from environmental damage. Skin wounds lead to microbial infection and harmful agent injury. Thus, wound repair is crucial for the recovery of the normal function of skin tissue. The present study investigated the promoting effects of spirulina protein (SPcP) in mice on skin wound repair and also aimed to elucidate the potential underlying mechanisms. The results revealed that SPcP promoted the skin wound repair in a mouse model of full-thickness excisional wounds. SPcP induced an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Wound healing begins immediately after injury with an increase in pro-inflammatory mediators and cells. This is followed by an increase in proliferation, transdifferentiation, and migration of fibroblasts to the injured site, production of dermal and epidermal cells, and synthesis of collagen and the extracellular matrix to re-establish the skin barrier [133]. The role of Spirulina extracts in fibroblast proliferation and wound healing has been described for years [128,132,133].…”
Section: Anti-oxidativementioning
confidence: 99%
“…Wound healing begins immediately after injury with an increase in pro-inflammatory mediators and cells. This is followed by an increase in proliferation, transdifferentiation, and migration of fibroblasts to the injured site, production of dermal and epidermal cells, and synthesis of collagen and the extracellular matrix to re-establish the skin barrier [133]. The role of Spirulina extracts in fibroblast proliferation and wound healing has been described for years [128,132,133].…”
Section: Anti-oxidativementioning
confidence: 99%
“…It was found that Spirulina protein enhances wound repair stimulating PI3K/Akt and EGFR/ERK pathways, which regulate cell cycle, proliferation, and migration. Furthermore, it inhibits the excessive formation of ROS, increasing SOD and CAT activity and reducing lipid peroxidation in tissue granulation 41 …”
Section: Wound Healing and Skin Regenerationmentioning
confidence: 99%
“…Furthermore, it inhibits the excessive formation of ROS, increasing SOD and CAT activity and reducing lipid peroxidation in tissue granulation. 41 A pectin isolated from S. maxima (SmP) demonstrated to also take part in wound-healing activity. Beyond in vitro, this was showed in vivo in zebrafish models.…”
Section: Wound He Aling and S Kin Reg Ener Ati Onmentioning
confidence: 99%
See 2 more Smart Citations